Marriage Agreements Following Constitutional Court Decision Number 69/PUU/XII/2015: Normative Implications for the Protection of Joint Property - Maya Duwi Ayunda; M. Asrafil; M. Iqbal Maulana Putra; Fery Adi Alwiyon; Saiin, Asrizal (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2025)
The Constitutional Court Decision No. 69/PUU-XII/2015 marked a significant legal reform in Indonesia’s marriage law by amending Article 29 of Law No. 1 of 1974 concerning Marriage, which previously restricted the making of prenuptial agreements to before or at the time of marriage. Following this decision, spouses are now permitted to create or amend marital agreements during the course of their marriage. This study aims to examine the normative implications of this ruling, particularly in relation to the protection and management of joint marital property. Using a normative juridical method with statutory and conceptual approaches, this research analyzes how the decision reshapes the legal framework governing marital property arrangements and enhances the protection of individual and joint ownership rights within marriage. The findings reveal that the Constitutional Court’s interpretation expands the legal meaning of marital agreements, providing greater flexibility and legal certainty for married couples in managing their assets. Nevertheless, challenges remain in its practical implementation, particularly concerning the registration process, the recognition of third-party rights, and the potential emergence of legal uncertainty if not properly regulated. Therefore, additional technical and procedural guidelines are necessary to ensure that the objectives of fairness, legal certainty, and protection of property rights can be effectively realized in accordance with the spirit of the Constitutional Court’s decision.